Preserved Tool Knowledge in the Context of Impaired Action Knowledge: Implications for Models of Semantic Memory - Garcea, Frank E.; Dombovy, Mary; Mahon, Bradford Z. (Frontiers in Human Neuroscience, 2013)
A number of studies have observed that the motor system is activated when processing the semantics of manipulable objects. Such phenomena have been taken as evidence that simulation over motor representations is a necessary and intermediary step in the process of conceptual understanding. Cognitive neuropsychological evaluations of patients with impairments for action knowledge permit a direct test of the necessity of motor simulation in conceptual processing. Here, we report the performance of a forty-seven year-old male individual (Case AA) and six age-matched control participants on a number of tests probing action and object knowledge. Case AA had a large left hemisphere frontal-parietal lesion and hemiplegia affecting his right arm and leg. Case AA presented with impairments for object-associated action production, and his conceptual knowledge of actions was severely impaired. In contrast, his knowledge of objects such as tools and other manipulable objects was largely preserved. The dissociation between action and object knowledge is difficult to reconcile with strong forms of the embodied cognition hypothesis. We suggest that these, and other similar findings, point to the need to develop tractable hypotheses about the dynamics of information exchange among sensory, motor and conceptual processes.